From Grain to Pixel The Archival Life of Film in Transition THIRD REVISED EDITION - Fossati, Giovanna (Amsterdam University Press, 2018)
"In From Grain to Pixel , Giovanna Fossati analyzes the transition from analog to digital film and its profound effects on filmmaking and film archiving. Reflecting on the theoretical conceptualization of the medium itself, Fossati poses significant questions about the status of physical film and the practice of its archival preservation, restoration and presentation. From Grain to Pixel attempts to bridge the fields of film archiving and academic research by addressing the discourse on film's ontology and analyzing how different interpretations of what film is affect the role and practices of film archives. Ultimately, Fossati proposes a novel theorization of film archival practice as the starting point for a renewed dialogue between film scholars and film archivists. Almost a decade after its first publication, this updated edition covers the latest developments in the field. Besides a new general introduction, a new conclusion and extensive updates to each chapter, a novel theoretical framework and a new case study have been added. Giovanna Fossati is chief curator at EYE Filmmuseum and professor of film heritage and digital film culture at the University of Amsterdam."